Toxicity of Anti-Inflammatory Substances in Hemigraphis Alternata Leaves: In Silico Study Using ProTox-II - Yeni Yeni; Rizky Arcinthya Rachmania (Jurnal Sains dan Kesehatan, 2023)
Hemigraphis alternata is empirically used to treat wounds. Hemigraphis alternata leaves ethyl acetate extract can assist in resolving the inflammatory process by inhibiting enzymes that play a role in the inflammatory cycle. Twenty-two substances found in the leaves of Hemigraphis alternata were predicted to have an anti-inflammatory effect by inhibiting cyclooxygenase-1 (COX-1) or 5-lipoxygenase (5-LOX) as an enzyme target. In-silico toxicology was carried out to acquire new anti-inflammatory drugs with low toxicity from 22 compounds. ProTox-II was utilized to measure the level of toxicity of these drugs at many endpoints. In this study, five compounds have LD50 > 5000 mg/kg body weight, toxicity class 5-6, and inactive for cytotoxicity, carcinogenicity, hepatotoxicity, mutagenicity and immunotoxicity parameters. They are 2-methyleneoctanenitrile, nerolidol, 2,7-dioxa-tricyclo[4.4.0.0(3,8)]deca-4,9-diene, 9,9-dimethoxybicyclo[3.3.1]nonane-2,4-dione, and phytol. Keywords:          in silico, toxicity, Hemigraphis alternata, anti-inflammatory, ProTox-II